Learning to see and understand developing visual literacy. (White Plains, N.Y. Center for Humanities, 1973)
Explores works by Leonardo da Vinci, Goya, Lichtenstein, Bierstadt, Picasso, Wyeth, Kelly, Albers and Matisse to show how great artists have expressed their feeling in their works.
Available also in VDR-328. 1 videocassette (42 min.) : sd., col. + 1 program guide.
Keywords: Communication; Visual literacy; Visual perception; Humanities; Art studies